The Complement System at the Embryo Implantation Site: Friend or Foe? - Bulla, Roberta; Bossi, Fleur; Tedesco, Francesco (Frontiers in Immunology, 2012)
An inflammatory-like process and vascular remodeling represent the main changes that occur in decidua in the early phase of pregnancy. These changes are partly induced by trophoblast cells that colonize the decidua and are also contributed by the complement system. C1q is one of the component components produced at feto-maternal interface that serves an important function in placental development. Decidual endothelial cells synthesize and express C1q on the cell surface where it acts as a molecular bridge between endovascular trophoblast and endothelial cells. C1q is also produced by extravillous trophoblast and is used to favor trophoblast migration through the decidua. C7 is another component produced and expressed on the membrane of endothelial cells and is involved in the control of the proinflammatory effect of the terminal complement complex. Defective expression of C1q by trophoblast is associated with impaired trophoblast invasion of decidua and may have important implications in pregnancy disorders such as preeclampsia characterized by reduced vascular remodeling. Local control of complement activation by several complement regulators including cell-bound C7 is critical to prevent complement-mediated tissue damage as suggested by recent data showing an association of preeclampsia with mutations in the genes encoding for some complement regulators.